A Novel Recurrent Neural Network to Classify EEG Signals for Customers' Decision-Making Behavior Prediction in Brand Extension Scenario - Ma, Qingguo; Wang, Manlin; Hu, Linfeng; Zhang, Linanzi; Hua, Zhongling (Frontiers in Human Neuroscience, 2021)
It was meaningful to predict the customers’ decision-making behavior in the field of market. However, due to individual differences and complex, nonlinear natures of the EEG signals, it was hard to classify the EEG signals and to predict customers’ decisions by using traditional classification methods. To solve the aforementioned problems, a recurrent t-distributed stochastic neighbor embedding (t-SNE) neural network was proposed in current study to classify the EEG signals in the designed brand extension paradigm and to predict the participants’ decisions (whether to accept the brand extension or not). The recurrent t-SNE neural network contained two steps. In the first step, t-SNE algorithm was performed to extract features from EEG signals. Secondly, a recurrent neural network with long short-term memory (LSTM) layer, fully connected layer and SoftMax layer was established to train the features, classify the EEG signals as well as predict the cognitive performance. The proposed network could give a good prediction with accuracy around 87% . Its superior in prediction accuracy as compared to a recurrent principal component analysis (PCA) network, a recurrent independent component correlation algorithm (ICA) network, a t-SNE- support vector machine (SVM) network, a t-SNE back propagation (BP) neural network, a deep LSTM neural network and a convolutional neural network was also demonstrated. Moreover, the performance of the proposed network with different activated channels were also investigated and compared. The results showed that the proposed network could make a relatively good prediction with only 16 channels. The proposed network would become a potential useful tool to help a company in making marketing decisions and to help uncover the neural mechanisms behind individuals’ decision-making behavior with low cost and high efficiency.